Analisis Tinjauan Hukum Terhadap Penetapan Hak Asuh Anak Yang Dibawah Umur Berdasarkan Yang Terbaik Bagi Anak - Ventaria Yulia, Erika; Adha, Lalu Hadi (Private Law, 2024)
This study aims to determine the legal arrangements for child custody of minors due to divorce and the legal considerations of Religious Court judges in determining the best child custody for minors. The research used a normative research method. The results of the research were first in the case of Decision Number 36/Pdt.G/2023/PA.Smn, where the custody of the child went to his mother because he was still a minor. Furthermore, in the case of the second decision, Number 183/Pdt.G/2021/PA.Mdo, the child custody rights went to the father because the mother had died and there were still biological parents, that is, the father, so the judge considered the best child custody rights to the father even though the child was still underage. There is no law that strictly and clearly regulates the obligation for child custody to be given to the biological mother or biological father after a divorce; the only rule that regulates this matter is in the Compilation of Islamic Law (KHI) Article 105, where it is stated that the control of child custody for children under 12 years of age is given to the biological mother. Based on the results of this study, in Islamic law, there is no dispute over fighting over child custody for divorced parents, who have the right to take care of and protect their children; it must be given to the mothers